2016
DOI: 10.3897/zse.92.9521
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of the deep-sea colonial ascidian Synoicum molle (Herdman, 1886): first record since its original finding during the Challenger Expedition

Abstract: The colonial ascidian Synoicum molle (Herdman, 1886) was recorded for the first time after its original description. The slope area where S. molle was discovered during the Challenger Expedition (1872-1876), located at the mouth off Río de La Plata (Argentine Sea), still remains highly underexplored. During a series of deep-sea prospections along the SW Atlantic (A.R.A. Puerto Deseado, August 2012), 7 colonies of S. molle were collected few km from the type locality. The finding permitted to perform, for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Observations: collected at HMS Challenger st. 320, which is the type locality of this species (Herdman 1886: 194-195) and recently found and redescribed off Mar del Plata at 308 m depth, i.e., relatively close to the type locality (Maggioni et al 2016: 181-185). Van Name (1945) included this species tentatively in the genus Synoicum, a denomination that Maggioni et al (2016) confirmed.…”
Section: Genus Synoicum Phipps 1774mentioning
confidence: 94%
See 2 more Smart Citations
“…Observations: collected at HMS Challenger st. 320, which is the type locality of this species (Herdman 1886: 194-195) and recently found and redescribed off Mar del Plata at 308 m depth, i.e., relatively close to the type locality (Maggioni et al 2016: 181-185). Van Name (1945) included this species tentatively in the genus Synoicum, a denomination that Maggioni et al (2016) confirmed.…”
Section: Genus Synoicum Phipps 1774mentioning
confidence: 94%
“…Aplidium incrustans Herdman 1886, also described from material of the HMS Challenger st. 320, has been referred by Van Name (1945) as a possible junior synonym of S. molle although stating that both species are poorly characterized. Maggioni et al (2016) (Lesson, 1830) Holozoa cylindrica Lesson, 1830: 439. For synonymy see Kott (1969: 29) and Monniot C. & Monniot F. (1983: 36). References and bathymetric distribution in Uruguayan waters: Barranguet (1988): not detailed, between 37-110 m.…”
Section: Genus Synoicum Phipps 1774mentioning
confidence: 99%
See 1 more Smart Citation
“…Although submarine canyons are known to be hotspots of benthic biomass and are globally numerous, these environments are very poorly sampled (Del Río Iglesias et al 2012), therefore it is very important to study their biodiversity. Based on the specimens collected during the expeditions to the canyon (2012 and 2013), several new records and new species of Cnidaria Verrill, 1865, Mollusca Linnaeus, 1758 and Echinodermata Bruguière, 1791 have already been published (Cerino & Lauretta 2013;Martinez et al 2014;Farías et al 2015;Signorelli & Pastorino 2015;Maggioni et al 2016;Pastorino & Sánchez 2016;Pastorino 2016Pastorino , 2019Martinez & Penchaszadeh 2017;Pereira & Doti 2017;Bernal et al 2018). Here, we describe a new species of Umbellula from Mar del Plata Submarine Canyon based on specimens collected between 2934 m and 3282 m deep, using both morphological and molecular data.…”
Section: Introductionmentioning
confidence: 82%
“…Van Name (1945) acknowledged the inadequacy of the original description for a proper species identification. The present material allowed to perform the first exhaustive and complete morphological description of S. molle (see Maggioni et al 2016). (Figure 7).…”
Section: Genus Synoicum Phipps 1774mentioning
confidence: 99%